Application of Persistent Scatterer Interferometry method (PSI) in Limón, Costa Rica - Paniagua-Jiménez, Diana Ninette; Valverde-Calderón, José; Molina-Calderón, Paula; Barrantes-Castillo, Gustavo (Revista Geográfica de América Central., 2021)
The objective of the present research was to apply the Persistent Scatterer Interferometry (PSI) method in the city of Limón, Costa Rica, in order to estimate surface deformation velocity. The investigation is of descriptive nature and use is made of radar imagery from the Sentinel-1 mission pre-processed with SNAP software of the European Space Agency. Line-of-sight (LOS) velocity and time series were estimated using the StaMPS software resulting in velocities in the range of -11 mm/yr5 to +20 mm/yr. It is concluded that the method has practical potential in Costa Rica for surface dynamics research and instances where no data is available from other methods such as GNSS.